Participatory Cost Estimation for the Rehabilitation of Uninhabitable Houses for Stimulant Assistance Recipients in Agam Regency, Indonesia - Yulcherlina; Edwina Zainal; Elfida Agus (Teras Jurnal : Jurnal Teknik Sipil, 2026)
Abstract   This study identifies the physical conditions and cost requirements for housing stimulant assistance for uninhabitable houses (RTLH) in Agam Regency, West Sumatra. A mixed-methods approach was employed, combining surveys, observations, and cost analysis of 76 BSPS recipient units across 15 villages. The findings reveal that 35–45% of assisted houses remain substandard, with sanitation, ventilation, and flooring as the most deficient components. Actual rehabilitation costs range from IDR 35–50 million per unit, significantly exceeding the IDR 20 million government stimulus, creating a funding gap of IDR 17.5–27.5 million per unit. Community self-reliance averages only IDR 8.45 million, insufficient to bridge this gap. The study contributes a participatory cost estimation framework integrating local knowledge to improve cost accuracy and programme targeting. Recommendations include increasing stimulus amounts, adopting participatory budgeting, and strengthening community participation. These findings inform policy improvements for more effective housing assistance programmes.   Keywords: Uninhabitable houses, housing stimulant assistance, rehabilitation costs, funding gap, participatory cost estimation     Abstrak   Penelitian ini mengidentifikasi kondisi fisik dan kebutuhan biaya bantuan stimulan perumahan bagi rumah tidak layak huni (RTLH) di Kabupaten Agam, Sumatera Barat. Metode campuran digunakan, menggabungkan survei, observasi, dan analisis biaya terhadap 76 unit penerima BSPS di 15 nagari. Temuan menunjukkan bahwa 35–45% rumah yang telah dibantu masih berada di bawah standar kelayakan, dengan sanitasi, ventilasi, dan lantai sebagai komponen paling defisien. Biaya rehabilitasi aktual berkisar antara Rp35–50 juta per unit, jauh melebihi bantuan pemerintah sebesar Rp20 juta, sehingga menimbulkan kesenjangan pendanaan sebesar Rp17,5–27,5 juta per unit. Swadaya masyarakat rata-rata hanya Rp8,45 juta, tidak cukup untuk menutupi kesenjangan tersebut. Penelitian ini menyumbangkan kerangka estimasi biaya partisipatif yang mengintegrasikan pengetahuan lokal untuk meningkatkan akurasi biaya dan ketepatan sasaran program. Rekomendasi meliputi peningkatan nilai bantuan, penerapan anggaran partisipatif, dan penguatan partisipasi masyarakat. Temuan ini memberikan masukan bagi perbaikan kebijakan program bantuan perumahan yang lebih efektif.   Kata kunci: rumah tidak layak huni, bantuan stimulan perumahan, biaya rehabilitasi, kesenjangan pendanaan, estimasi biaya partisipatif